PENGARUH PENGUNGKAPAN STRUKTUR CORPORATE GOVERNANCE TERHADAP KECURANGAN PELAPORAN KEUANGAN - Widodo, Arief; Syafruddin, Mochamad (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the effect of corporate governance structure on the likelihood of fraudulent financial reporting. The dependent variable used in this study is fraudulent financial reporting. Meanwhile, independent variables used in this study are the disclosure of corporate governance structure such as the number of the board of commissioners member, board members with international experiece, audit committee effectiveness, internal audit effectiveness, and the existence of Big-4 audit firms. The population in this study consists of all manufacturing companies listed in Indonesia Stock Exchange during 2014-2015. The sampling method used is purposive sampling. The total number of samples in this study were 242 companies. Data analysis was performed by the descriptive statistic analysis and hypothesis test with logistic regression analysis.The result of this study shows that board members with the international experience, audit committee effectiveness, internal audit effectiveness, and the existence of Big-4 audit firms have significant positively effect in reducing the likelihood of fraudulent financial reporting. However, the number of the board of commissioners member have no significant effect on the likelihood of fraudulent financial reporting